Effect of Cold Water Immersion on Physical Recovery and Athletic Performance in Elite Professional Footballers. - Setaouti, Mohamed Djamel Zddine; Khiat, Belkacem; Kasmi , Mohamed El Bachir (sports creativity, 2025)
The aim of this study was to compare the impact of cold water immersion recovery on the perception of muscle recovery in professional footballers. Twenty professional footballers from USMO Oran were divided into two groups: an immersion group (COLD) and a control group (NO). After the training session (lower limb strength training and games), each player reported their muscle sensations via a questionnaire. This sensation was reassessed over the following three days. The results indicate a significant difference. Conclusion: Cold water immersion improves the physical fitness and muscle strength of young footballers.